2006
DOI: 10.1002/bit.21036
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable cationic polyester as an efficient carrier for gene delivery to neonatal cardiomyocytes

Abstract: Viral-mediated gene delivery has been explored for the treatment and protection of cardiomyocytes, but so far there is only one report using cationic polymer for gene delivery to cardiomyocytes in spite of many advantages of polymer-mediated gene delivery. In this study, a cationic poly(b-amino ester) (PDMA) with a degradable backbone and cleavable side chains was synthesized by Michael addition reaction. The toxicity of PDMA to neonatal mouse cardiomyocytes (NMCMs) was significantly lower than that of polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…They have low toxicity and have been used for gene delivery because they generally carry cationic charges in water (Akinc et al 2003;Anderson, Lynn, and Langer 2003;Little et al 2004Little et al , 2005Shenoy et al 2005). We found that the polymerization of 2,2-bis(acryloxymethyl)propionic acid with amine monomers produced carboxylic acid-functionalized zwitterionic polymers (Xu et al 2006a). The polymer is water soluble and degradable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They have low toxicity and have been used for gene delivery because they generally carry cationic charges in water (Akinc et al 2003;Anderson, Lynn, and Langer 2003;Little et al 2004Little et al , 2005Shenoy et al 2005). We found that the polymerization of 2,2-bis(acryloxymethyl)propionic acid with amine monomers produced carboxylic acid-functionalized zwitterionic polymers (Xu et al 2006a). The polymer is water soluble and degradable.…”
Section: Discussionmentioning
confidence: 98%
“…The graft polymers were synthesized by cocondensation polymerization of 2,2-bis(acryloxymethyl)propionic acid and PEG with terminal 2,2-bis(acryloxymethyl)propionate with piperazine (Xu et al 2006a). The same type of diacrylates was used to make the PEG chains randomly distributed along the polymer backbones.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Liu and Reineke used poly (glycoamidoamine)s as carriers for gene delivery to cardiomyoblast cells [80], while Xu et al evaluated the transfection ability of a new poly ( -aminoester) derivative with pEGFP on neonatal mouse cardiomyocytes [81].…”
Section: Types Of Nonviral Vectorsmentioning
confidence: 99%
“…[86][87][88] The main disadvantage is that PEG is not cell-specific, and one would need very high doses in order to achieve the desired concentration, leading to potentially serious side effects. 89,90 Thus, the need to improve current knowledge in the field and to produce other ligand molecules for aptamers functionalization. Aptamers are short, single-stranded oligonucleotides formed by 30-50 bases and they express minimal or even no antigenicity and immunogenicity, making them more suitable for in vivo use in clinical hematology and oncology.…”
Section: Nanocarriers Conjugated With Mirnas or Anti-mirna Oligonuclementioning
confidence: 99%